Design and construction of a photoresistive sensor for monitoring the rat vibrissal displacement - Dürig, Federico (2009)
Rats sweep their vibrissae in a rhythmic and coordinated fashion in order to acquire tactile information from their environment. Measuring vibrissae movement has become a matter of increased attention, from several labs, over the last few years. We describe the design and construction of an inexpensive photoresistive sensor that registers horizontal vibrissae movement. The device consists of an LED array and a light-dependent resistor (LDR) covered by a coating with varying transparency along its axis. When a vibrissa is located in the sensor, it generates a shadowy line over the photosensitive material, thus changing the LDR resistance. These changes are transduced into voltage changes. Our measurements on vibrissa show that this simple and inexpensive sensor effectively monitors the movement of a single vibrissa.